Criminal and Civil Aspects Of Healthcare Worker Liability For Medical Malpractice in Croatia - Šago, Dinka (Medicine, Law & Society, 2023)
A healthcare worker’s liability for damage caused to patients can be criminal, civil, misdemeanour, and disciplinary, with the necessary precondition that the damage was caused as a result of medical malpractice or negligence, and not as a result of the regular course of the disease. The paper analyzes the criminal law and civil law aspects of the healthcare worker’s responsibility for damage caused by medical malpractice through the provision of medical care. The imprecise definition of the legal nature of the healthcare worker’s responsibility, the obligations that the law imposes on doctors, the definition of malpractice in medical treatment, as well as the legal basis of responsibility, indicate the existence of many legal dilemmas that require additional analysis to which we would like to contribute with this paper. Because of a broad concept of issues in healthcare worker’s liability, this paper aims to explain the material assumptions of criminal (duty to act) and civil (negligence) liability and discusses the legal position of a medical expert in both types of proceedings.